TINJAUAN YURIDIS MOSI TIDAK PERCAYA KEPADA KETUA DPRD KOTA PEKANBARU BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Haris Vivera Simatupang; Mexsasai Indra; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research is related to the Juridical Review of the vote of no confidence in the chairman of the Pekanbaru City House of Representatives by its members which was reviewed based on the laws and regulations in Indonesia. The vote of no confidence is one of the efforts used to overthrow the government in parliamentary countries. While Indonesia is a country whose form of government is presidential, it needs to be studied stimulantly. First, how is the mechanism for replacing the chairman of the Pekanbaru City People's Representative Council based on laws and regulations, Second, the implications of a motion of no confidence in the chairman of the Pekanbaru People's Representative Council based on laws and regulations. This research is a sociological legal research, because it is based on field research, namely by collecting data from observations, interviews and literature reviews that are related to the problems studied, assisted by primary, secondary and tertiary data. This study uses quantitative analysis, produces descriptive data and From the results of this study, it was concluded that,, the First mechanism for replacing the chairman of the Pekanbaru City House of Representatives based on laws and regulations does not regulate through a vote of no confidence. Reimbursement can only be made through the DPRD honorary body after the honorary body has investigated, verified and clarified the complaint. Second, the implication of the motion of no confidence in the chairman of the Pekanbaru City DPRD is only as a moral sanction, a warning for a better future.Keywords = Juridical Review - No Confidence Motion - Pekanbaru City Regional People's Representative Counci